By the Honourable Spencer Phips, Esq ; ... A proclamation for proroguing the General Assembly : ... to the ninth day of January next ... Given at the Council-chamber in Boston, the seventh day of December, 1750 . (Printed by John Draper, printer to his honour the lieutenant-governour and Council, 1750)
December 7, 1750 Proclamation of Lieutenant-Governor Spencer Phips regarding the prorogation of the General Assembly, previously scheduled to meet on December 19th, postponed until January 9th.